Business Process Transformation. - Grover, Varun (Taylor and Francis, 2015)
Featuring contributions from prominent thinkers and researchers, this volume in the ""Advances in Management Information Systems"" series provides a rich set of conceptual, empirical, and introspective studies that epitomize fundamental knowledge in the area of Business Process Transformation. Processes are interpreted broadly to include operational and managerial processes within and between organizations, as well as those involved in knowledge generation. Transformation includes radical and incremental change, its conduct, management, and outcome. The editors and contributing authors pay clo.